1995
DOI: 10.1016/0735-1097(95)80031-b
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of fetal cardiac tumors: a multicenter experience and review of published reports

Abstract: Fetal cardiac tumors, a rare condition, are often benign. The majority of tumors are rhabdomyomas, but not all fetuses with rhabdomyoma have tuberous sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
201
0
7

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(210 citation statements)
references
References 29 publications
2
201
0
7
Order By: Relevance
“…2 Rhabdomyomas are the most common tumors, accounting for about 50% of all cases in children. 3 A strong association with tuberous sclerosis has been reported.…”
mentioning
confidence: 99%
“…2 Rhabdomyomas are the most common tumors, accounting for about 50% of all cases in children. 3 A strong association with tuberous sclerosis has been reported.…”
mentioning
confidence: 99%
“…Conjoined twinning is a rare condition, occurring in 1 in 200 000 pregnancies 1 . Conjoined twins have been reported in association with in-vitro fertilization (IVF) and assisted hatching 2 and intracytoplasmic sperm injection 3 , but not blastocyst transfer.…”
Section: First-trimester Diagnosis Of Conjoined Twins After In-vitromentioning
confidence: 99%
“…Cardiac tumors are rare; the prevalence, reported from autopsy studies of patients of all ages, varies from 0.0017% to 0.28% 1 . Rhabdomyoma is the most common benign fetal cardiac neoplasm, whereas hemangioma is extremely rare, occurring at a frequency of only 1 in 19 cardiac tumors 1 . Fetal cardiac hemangioma usually arises from the atrial wall or pericardium.…”
mentioning
confidence: 99%
“…With the constant improvement of ultrasonographic technology and the improved knowledge of diagnostic ultrasonography, early cardiac tumors may be accurately detected (24). However, this should be differentiated with strong echo spots in the ventricular cavity and certain normal heart structures, such as the small papillary muscle (25). Therefore, it should be dynamically and closely followed up in order to avoid misdiagnosis or missed diagnosis (21).…”
Section: A B C D a Bmentioning
confidence: 99%
“…However, it is reported that the recurrence rate is ≤50% (24) and the prognosis is poor. Thus, pregnancy should be terminated when recurrence is identified (25), as a more serious hemodynamic disorder is also likely to occur in the neonatal period and lead to neonatal mortality or neurological symptoms, or other severe complications (26). Therefore, all patients in the present study were constantly followed up prior to the time of writing.…”
Section: A B C D a Bmentioning
confidence: 99%